P0156SHORT-TERM BLOOD PRESSURE VARIABILITY IN DIABETIC AND NON-DIABETIC PATIENTS WITH CKD STAGE 2, 3A, 3B AND 4. (6th June 2020) - Schoina, Maria; Loutradis, Charalampos; Minopoulou, Ioanna; Theodorakopoulou, Marieta; Dimitroulas, Theodoros; Doumas, Michael; Garyfallos, Alexandros; Karagiannis, Asterios; Papagianni, Aikaterini; Sarafidis, Panteleimon
Abstract: Background and Aims: Blood pressure variability (BPV) is an important risk factor for cardiovascular events and mortality in patients with chronic kidney disease (CKD). Previous evidence suggests that BPV is gradually increasing across CKD stages. Whether type 2 diabetes mellitus (DM) is an additional risk factor for increased BPV has never been studied. The aim of this study is to examine in comparison BPV in diabetic and non-diabetic patients with CKD. Method: We included 48 diabetic and 48 non-diabetic adult patients (>18 years) with CKD (eGFR: <90 και ≥15mL/min/1.73m 2 ), matched in a 1:1 ratio for age, sex and eGFR within each CKD stage (2, 3a, 3b and 4). All patients underwent 24-hour ambulatory blood pressure (BP) measurement with the Mobil-O-Graph device. Brachial BP variability was calculated with validated formulas. We calculated standard deviation (SD), weighted SD (wSD), coefficient of variation (CV), and average real variability (ARV) of BP during the 24-hour, day- and night-time periods with validated formulas. Results: In total population, ambulatory systolic BP (SBP) levels were significantly higher in diabetics compared to non-diabetic counterparts in all studied periods. No significant differences were evidence for ambulatory diastolic BP (DBP) in total or across CKD stages. In total, 24-hour SBP SD (15.43±4.34 vs 13.38±3.35, p=0.011), wSD (14.41±4.11 vs 12.53±3.19, p=0.014) and ARV (10.94±2.75 vs 9.46±2.10, p=0.004) were higher in patients with DM compared to those without DM. In addition, 24hour DBP SD (11.04±2.39 vs 9.80±2.28, p=0.010), wSD (10.30±2.52vs 9.05±1.99, p=0.008), CV (14.77±3.05 vs 13.14±2.96, p=0.009) and ARV (8.23±2.10 vs 7.10±1.33, p=0.002) were again different between groups. Across CKD stages 2 and 3a, BPV indices were insignificantly higher in patients with DM. In CKD Stage 3b, 24-hour SBP-SD (16.30±4.52 vs 11.35±2.62, p=0.003), wSD (15.42±4.54 vs 10.77±2.30, p=0.004), ARV (12.46±3.19 vs 8.34±2.07, p=0.001) and 24-hour DBP-CV (14.84±3.63 vs 12.18±1.91, p=0.035) were higher in diabetic compared to non-diabetic patients. In contrast, no difference between groups existed in CKD Stage 4. Conclusion: Patients with DM present increased BPV in CKD Stages 2, 3a and 3b (moderately impaired renal function). This difference is not apparent in patients with advanced CKD at Stage 4.